Ambrus Beds - Important Key for Interpretation of Neocomian Paleogeography, Sea-Level Changes, Depositional Setting and Tectonics in Suha Krajina Area (Slovenia) - Dozet, Stevo (Geologija, 1996)
The lower part of the Lower Cretaceous stratigraphic sequence at Ambrus, composed of limestones, dolomitic limestones, dolomites, intertidal breccias and overlying heterogeneous carbonate breccias is described in this paper. On the basis of stratigraphic order, fossil contents as well as the well-determined fossiliferous underlying Upper Malm and overlying Barremian carbonate sediments, the formation denominated the Ambrus beds was ascribed to the Neocomian. Fenestral limestones, laminated limestones and dolomites containing stromatolites, mudcracks and numerous erosion and oxidation surfaces are interpreted as tidal Storm deposits. The shallow water sediments, the breccias and the subaerial exposures, evidenced by relatively common karstification phenomena, are considered to be connected with eustatic sea-level variations and epeirogenetic movements. The lithology and areal distribution of these deposits indicate a sedimentation in a relatively symmetric, rather shallow lagoon. The breccias composed of various poorly sorted angular and subangular limestone and dolomite fragments, as well as of calcitic and dolomitic cement, have been attributed to tidal and cliff breccias. The majority of the breccia fragments indicate a pretty shallow water and subaerial sedimentation conditions.